Guarding the Gift of Freedom - Clay, Lucius D. (Lucius DuBignon) (Tufts Archival Research Center, 2006)
Lucius D. Clay describes being inspired by the German people's desire for democracy following World War II and believes that all people want peace and liberty and also believes freedom is a privilege given by God, and one that must be carefully guarded by all citizens and he calls upon Americans to make this country one that provides equal opportunities for all.